Intention to Use and Over-Ordering in Online Food Delivery Services: An Extension of the Theory of Planned Behavior - Permasih, Desta; Suroso, Arif Imam; Hasanah, Nur (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
Online food delivery (OFD) services can shape consumer habits through regular use. Although promotions attract consumers, they may also encourage food waste. This study analyzes factors influencing the intention to use OFD services and over-ordering behaviors by extending the Theory of Planned Behavior (TPB) with variables such as sales promotion and leftover reuse. The study used purposive sampling and collected data from an online survey of 253 OFD service users in Jabodetabek. Descriptive analysis and Partial Least Squares-Structural Equation Modeling (PLS-SEM) were applied. Results showed that most of the OFD users in this study were female residents of Bogor and Jakarta, aged 25 - 35 years old, single, holding a bachelor's degree, employed, with monthly incomes of IDR5,000,000 and IDR10,000,000, and spending IDR1,000,000 - IDR2,000,000 per month on food. Intention to use was influenced by attitude and subjective norms, while over-ordering was influenced by sales promotion and intention to use. The leftover reuse variable did not significantly influence the intention to use or over-ordering. Implications include encouraging continued OFD use through targeted advertising and features to help users manage consumption behavior, such as setting order reminders, providing nutritional information, and offering personalized portion recommendations. This study’s novelty lies in introducing a new variable and demonstrating that sales promotions can encourage over-ordering.